2007
DOI: 10.1016/j.biomaterials.2007.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Growing a living blood vessel: Insights for the second hundred years

Abstract: Cardiovascular disease continues to be the leading cause of death worldwide, and the prevalence of cardiovascular disease has reached epidemic proportions worldwide. Not surprisingly this has led to an increasing number of vascular procedures annually. Unfortunately, the success of these procedures over time continues to limit their long-term effects. Biomedical engineering approaches to improve upon current prosthetic grafts, developing new prosthetic grafts, and creating tissue engineered blood vessels for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 26 publications
0
40
0
1
Order By: Relevance
“…In the meantime, the recruitment of SMCs is vital to stabilize the newly formed endothelium 32, 39, 40, 41, 42. In this study, we have demonstrated that the inclusion of 7A, especially the phosphorylated version 7Ap, significantly increased endothelialization.…”
Section: Discussionmentioning
confidence: 53%
“…In the meantime, the recruitment of SMCs is vital to stabilize the newly formed endothelium 32, 39, 40, 41, 42. In this study, we have demonstrated that the inclusion of 7A, especially the phosphorylated version 7Ap, significantly increased endothelialization.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, we also consider the incorporation beneficial in its ability to accelerate the connection to the host capillary system. Moreover, it is believed that trans-interstitial capillary ingrowth from the adventia or peri-graft tissue wall, contributes to the endothelialization along the lumen of the graft (Brewster et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Durch die lokale Applikation von Zytokinen kann das Einsprossen von Kapillaren aus dem umgebenden Gewebe mit konsekutivem Einwachsen und Ausrichtung von Endothelzellen auf der luminalen Oberfläche erreicht werden. Die Endothelialisierung, ausgehend vom nativen Gefäß über die Anastomosen, erfolgt dagegen nur über eine sehr kurze Strecke [9].…”
Section: Synthetische Gefäßprothesenunclassified